Processing and characterization of carbon nanofibers obtained from PAN/lignin blends processed by electrospinning - Cintra, Isabela L. R. [UNESP] (2023)
Blankets based on blends with different PAN/lignin ratios (10 and 50% wt. of lignin) were processed via electrospinning. Then, the blankets obtained were thermally treated in order to produce samples of carbon nanofibers. The thermo-oxidative stabilization parameters were defined based on a 23-factorial design. The samples, after stabilization, were analyzed by differential scanning calorimetry (DSC), thermogravimetry (TGA), scanning electron microscopy (SEM), and Fourier transform infrared spectroscopy (FT-IR) techniques. Based on the results, the best parameters for the stabilization of electrospun, blankets were selected, and subsequently, the most adequate carbonization parameters were established to obtain the carbon blankets. The carbonized blankets were characterized for electrical conductivity by impedance spectroscopy, chemical structure (Raman and FT-IR spectroscopies), crystallographic ordering by X-ray diffraction (XRD), and morphology (SEM). The results showed the feasibility of producing carbon blankets based on PAN/lignin blends. However, carbonized blankets showed low carbon yield (10–56%) and a decrease of up to 70% in fiber diameter. XRD and Raman spectroscopy showed that the structural ordering of carbon blankets presents different values according to the heat treatment parameters used (45–57%) and a poorly ordered structure, indicated by the ID/IG ratio.